Hungarian Monitoring, 9 August 1988 . [Magyar rádiófigyelő], 1988. augusztus 9 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Iraq-Iran ceasefire latest events Domestic Affairs: - Károly Grósz reports to Political Committee on his Warsaw and America trips - Mayor of Bonn holds press conference - Employment, unemployment, unemployment benefits - Interview with US Ambassador Mark Palmer - Situation of Hungarians in Romania - Young people and Alliance of Young Democrats (Fidesz) Külpolitika: - Az iraki-iráni tűzszünet eseményei Belpolitika: - Grósz Károly beszámol varsói és amerikai útjáról a politikai bizottságban - A bonni főpolgármester sajtókonferenciája - Foglalkoztatás, munkanélküliség, munkanélküli segély - Interjú Mark Palmer nagykövettel - A romániai magyarság helyzete - Az ifjúság és a FIDESZ